2017
DOI: 10.18683/germs.2017.1117
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug and co-resistance patterns of non-fermenting Gram-negative bacilli involved in ventilator-associated pneumonia carrying class 1 integron in the North of Iran

Abstract: ConclusionThe high prevalence of multidrug resistance and incidence of class 1 integron is a therapeutic concern. Employing antibiotic stewardship in hospitals could prevent the dissemination of MDR bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(17 reference statements)
4
3
1
Order By: Relevance
“…In a worrying study of MDRAB antibiotic susceptibility, it was reported that the colistin resistance rate increased to 35.7% in Iran [19]. In the present study, while all isolates in 2015 were sensitive to colistin, colistin resistance was found to be at 3.8% in 2016.…”
Section: Discussioncontrasting
confidence: 37%
See 1 more Smart Citation
“…In a worrying study of MDRAB antibiotic susceptibility, it was reported that the colistin resistance rate increased to 35.7% in Iran [19]. In the present study, while all isolates in 2015 were sensitive to colistin, colistin resistance was found to be at 3.8% in 2016.…”
Section: Discussioncontrasting
confidence: 37%
“…In a study reported from Palestine, 40 isolates were obtained from NICU in 2004-2005, and 77.5% of them were found to be resistant to trimethoprim/sulfamethoxazole [13]. In 2 recent studies conducted in Iran and India, the trimethoprim/sulfamethoxazole resistance rate was detected as 92.5% and 73.3%, respectively [19,20]. In a recent survey describing secular trends in the resistance of 39,230 A. baumannii isolates in the United States from 2003 to 2012, it was stated that the rate of resistance to trimethoprim/sulfamethoxazole varied between 52.5-57.5% during the study period, and the total resistance rate was 55.3% [16].…”
Section: Discussionmentioning
confidence: 99%
“…us, the class 1 integron was related to intI1, but no significant difference was found in the carrying rate between the pandrug resistance phenotype and multidrug resistance phenotype (P > 0.05). Class 2 and 3 integrons were not detected in any of the strains, which agreed with previous reports [15][16][17][18]. erefore, class 2 and 3 integrons were not related to quinolone resistance in the tested strains.…”
Section: Discussionsupporting
confidence: 92%
“…Similar proportions were described in previously published studies from Spain, Iran, and Tunisia [48][49][50]. In this study, the rate of class 1 integrons among CR isolates was 73%, while in reports from Iran, this index was higher (86-95%) [51,52]. In our study, class 1 integrons were detected in 76% of MDR P. aeruginosa, 70% of MDR K. pneumoniae, 68% of MDR A. baumannii, and 34% MDR of E. coli.…”
Section: Discussionsupporting
confidence: 90%